(untitled) (International Journal of Technology and Management Research, 2021)
Technical and Vocational Education is imperative when considering the human resource development of a country. The challenges facing Technical and Vocational Education in the Eastern Region is the consistent diminution of students opting to pursue Technical and Vocational courses at the Secondary level of education. The study seeks to assess student’s low interest in choosing Technical programme at the Second Cycle Institutions in the Eastern Region of Ghana. The sampling technique used was stratified and simple random sampling. The research was a cross–sectional studies and field questionnaire survey was used to collect information for the study. Data was collected from one thousand, one-hundred and six (1,106) respondents. Data were analyzed using frequency, charts and other relative important Indexes. It was found out that students ‘have low interest in technical courses due to societal stigmatization against the programme. The concept of Vocationalization must be re–visited at the Basic levels of the educational system. Citation: Akorli, S. K. and Gyamfi, T. A. (2021). An Assessment of Students’ Interest in choosing Technical Programmes among First Cycle Institutions in the Eastern Region of Ghana. International Journal of Technology and Management. Research. Vol. 6, Issue 1: 1－13. Received: April 15, 2020 Accepted: March 30, 2021